PENGARUH UKURAN PERUSAHAAN, UMUR PERUSAHAAN, PROFITABILITAS, SOLVABILITAS, DAN PERTUMBUHAN PENJUALAN TERHADAP NILAI PERUSAHAAN - Vanesha Christy; Sufiyati Sufiyati (Jurnal Paradigma Akuntansi, 2023)
The purpose of this research is to determine the effect of firm size, firm age, profitability, leverage, and sales growth on the value of manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2020. This research is using 61 manufacturing companies for four years as a sample after selected by purposive sampling method from 198 companies. This research is using Eviews 12 SV software to process the data and using multiple linear regression analysis techniques to test the hypothesis. The result of this research shows that firm size, profitability and sales growth do not have significant effect on firm value while firm age and leverage has a negative and significant effect on firm value. The implication of this study is the need to increase the management performance so the old company can follow the current trend and the company leverage can decreasing, so that will bring a positive signal for investors which will increase the firm value.